A baseline model of industry evolution - Sidney G. Winter; Yuri M. Kaniovski; Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
The paper analyses the properties and outcomes of competitive dynamics in industries characterized by heterogeneous firms and continuing stochastic entry. A formal analytical apparatus is developed, able to derive some generic properties of the underlying competition process combining persistent technological heterogeneity, differential growth of individual firms and turnover.
Keywords: 330; Industriestruktur; Strukturwandel; Markteintritt; Stochastischer Prozess; Wettbewerb; Evolutionsökonomik; Theorie; Evolutionäre Spieltheorie